Analisis Performa Raytracing dan MCMC Pada Realisme Visualisasi Obyek 3D Dengan Terintegrasi MIPMapping - Budet, Vincensa Woytimena; Himamunanto, Agustinus Rudatyo; Budiati, Haeni (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
The development of computer graphics has resulted in an increasingly realistic and immersive digital world, especially in the field of 3D object representation. One of the techniques for image presentation is ray tracing, however, regular ray tracing requires long computation time. To achieve high realism in 3D objects, complex computational operations and the use of appropriate algorithms are required. In this research, Markov chain Monte carlo (MCMC) algorithm has the potential to achieve realism on a 3D object. This research analyzes the performance comparison between ordinary ray tracing and MCMC algorithm in achieving realism on 3D objects and integrating Mipmapping technology to improve the visual quality of 3D objects. The results are measured by calculating the PSNR value on the rendered object and comparing the noise level of a 3D object rendered with ordinary ray tracing, and ray tracing using the Monte carlo algorithm. The number of samples used were 50 samples of 3D objects tested with Monte Carlo and obtained a result of 94%, and with ordinary ray tracing of 6% which is indicated by the level of distortion or error that occurs in the processed object. This shows that by rendering using the MCMC algorithm the image quality of the rendered object is better than rendering using ordinary ray tracing